Characterization of Activated Carbon from Fabric Waste Activated by NaOH and NaCl - AS, Prawira David; Luciana, Luciana; Utami Susanto, Mutiara Putri (Sainteks: Jurnal Sain dan Teknik, 2024)
Abstract: There is a lot of waste on earth in the form of textile waste in the form of fabrics either from textile waste fabrics produced by convection or from used clothing. This study aims to utilize the textile waste fabric as raw material for making activated carbon. To determine the content of activated carbon from textile fabric waste, it would be better if the fabric is grouped according to its classification whether it includes fibers derived from cellulose fabrics or synthetic fabrics. This test is done by combustion test, dissolution test and microscope test. To calculate the content of activated carbon produced by using NaOH and NaCl activator substances of various concentrations of 8%, 10%, and 12% for 24 hours. Carbonization process temperature 480 ˚C for 5 minutes. Activated carbon analysis calculates: water value, ash value, iodine number analysis, volatile matter value, fixed carbon, and SEM test. The results of the research of activated carbon that meets the qualification standards of SNI activated carbon 06-3730-1995 are water value and ash value, while the value of iodine number, volatile matter, and fixed carbon has not met the standards.